1988
DOI: 10.1139/v88-121
|View full text |Cite
|
Sign up to set email alerts
|

A study of iron–tungsten oxides and iron–chromium–tungsten oxides

Abstract: A 57Fe Moessbauer study of the Fe2O3–WO3 and Fe2O3–Cr2O3–WO3 systems has been carried out. Single phase materials could be prepared having the composition Fe2−xWO6−3x/2 (x = 0.28), the stoichiometric Fe2WO6 always contained detectable amounts of α-Fe2O3. The iron tungstates are found to be unstable to prolonged heating at 1000 °C. The Cr2−yFeyWO6 (0 < y ≤ 2) system was shown to be of the trirutile type when y ≤ 1.7 but multiphasic when y ≥ 1.7, these latter phases have structures based upon the iron and chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…Mössbauer spectra of the as prepared electrode, after being soaked in the electrolyte (blank) and after 10,000 cycles are shown in Figure 7. The as prepared electrode spectrum agrees well with the data reported by Birchall et al for Fe 2 WO 6 powder [33]. The fitting was performed with an appropriate distribution of 6 Lorentzian profiles representing quadrupole doublets by least-squares methods (Figure S2).…”
Section: Mössbauer Spectroscopy Analysissupporting
confidence: 82%
“…Mössbauer spectra of the as prepared electrode, after being soaked in the electrolyte (blank) and after 10,000 cycles are shown in Figure 7. The as prepared electrode spectrum agrees well with the data reported by Birchall et al for Fe 2 WO 6 powder [33]. The fitting was performed with an appropriate distribution of 6 Lorentzian profiles representing quadrupole doublets by least-squares methods (Figure S2).…”
Section: Mössbauer Spectroscopy Analysissupporting
confidence: 82%
“…Historically, the interest in the properties of Fe 2 WO 6 was mostly focused on the magnetism and/or transport properties of its polymorphs, considered in the framework of the AB 2 O 6 structures combining a magnetic cation B with an A cation of high formal charge. In recent years, the environmentally benign character of iron has spurred the interest for iron-based oxides. Accordingly, Fe 2 WO 6 has become the focus of much more varied investigations regarding the photoelectrochemical activity, photocatalytic properties, reversible capacity as a lithium-ion battery electrode, , pseudocapacitance in electrochemical capacitors, magnetodielectric properties, thermoelectric properties, , and biological activity .…”
Section: Introductionmentioning
confidence: 99%
“…Some of them concern the polymorphism of Fe 2 WO 6 . Most of the older literature and all of the recent papers have focused on one polymorph only, usually either the high-temperature γ polymorph ,, or the α polymorph obtained by low-temperature solution routes. ,,,, In the early 90s, Walczak et al identified a third polymorph, labeled β, whose synthesis required long heat treatments; shortly afterward, Guskos et al , reported some magnetic and electric transport data for the three polymorphs. To date, their work remains the only comparative study of the α/β/γ polymorphs, and further work is needed to clarify the influence of the synthesis conditions on the polymorphism and on structural properties such as the cationic order/disorder.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations